La transferencia de conocimiento en la organización multiunidad: Un modelo integrado de análisis1 - Navas López, José Emilio; López Sáez, Pedro; PERONA ALFAGEME, María Del Mar (Cuadernos de Estudios Empresariales, 2010)
This theoretical paper proposes an integrated model for the identification, classification and analysis of the different determinants of knowledge transfer found in the literature. It considers simultaneously four groups of determinants which have been traditionally approached separately: Characteristics of knowledge, characteristics of the knowledge senders, characteristics of the knowledge receivers and characteristics of the context where the transfer evolves. The main contribution is the development of an integrated approach which contemplates simultaneously the different types of determinants to knowledge transfer. In this way it attempts to answer to the needs expressed in the recent literature. This model can be applied both to the analysis of knowledge transfer within the organisation or between companies.
Keywords: Knowledge transfer; Model